2011
DOI: 10.1007/s10517-011-1379-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Damage in Human Bone Marrow Cells and Multipotent Mesenchymal Stromal Cells

Abstract: We carried out a comparative analysis of DNA damage (percentage of DNA in comet tail) and frequencies of comets in apoptotic cells in BM samples and cultures of BM multipotent mesenchymal stromal cells at different terms of culturing (passages 3-11). The levels of DNA damage in mesenchymal stromal cells remained unchanged during culturing (3.5 ± 0.9 and 4.4 ± 1.2%) and did not differ from those in BM cells (3.6 ± 0.8%). In BM samples, 10-28% atypical cells with high level of DNA damage were detected. In mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Froelich et al (2013) also detected chromosomal aberrations by means of the chromosomal aberration test, even when the comet assay did not detect damage. This same finding is also reported by Nikitina et al (2011) andBochkov et al (2006).…”
Section: Discussionsupporting
confidence: 90%
“…Froelich et al (2013) also detected chromosomal aberrations by means of the chromosomal aberration test, even when the comet assay did not detect damage. This same finding is also reported by Nikitina et al (2011) andBochkov et al (2006).…”
Section: Discussionsupporting
confidence: 90%
“…However, studies for hMSCs report low levels of chromosomal aberrations among donor samples [15, 16] and during culture expansion [5, 17, 18]. Low levels of non-clonal chromosomal aberrations in MSCs used in clinical trials have been observed, but there are no reports of malignant transformation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they must be produced via a robust GMP process to ensure safety and efficacy: the validation of the process is a critical step, considering that living cells are bioresponsive and can rapidly react to changes of the culture environment. In particular, both MSC and ASC in culture are subject to genomic and/or chromosomal mutations and the karyotype can change (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). It has not yet been clarified in what culture conditions the mutations are most frequent, and the results obtained by independent research groups are often contradictory, as reviewed by Ferreira in 2012 (26).…”
mentioning
confidence: 99%